Microbiota-ear-brain interaction is associated with generalized anxiety disorder through activation of inflammatory cytokine responses - Feng, Renyi; Zhu, Qingyong; Li, Qingchen; Zhai, Yanping; Wang, Jiuqi; Qin, Chi; Liang, Dongxiao; Zhang, Rui; Tian, Haiyan; Liu, Han; Chen, Yongkang; Fu, Yu; et al. (Frontiers in Immunology, 2023)
Introduction Generalized anxiety disorder (GAD) is one of the most enduring anxiety disorders, being associated with increased systemic inflammation. However, the trigger and mechanisms underlying the activation of inflammatory cytokine responses in GAD remain poorly understood. Materials and methods We characterized the ear canal microbiome in GAD patients through 16S rRNA gene sequencing and metagenomic sequencing and identified the serum inflammatory markers in GAD patients. Spearman correlations were applied to test the relationship between the microbiota changes and systemic inflammation. Results Our findings showed the higher microbial diversity, accompanied with the significantly increased abundance of Proteobacteria, and decreased abundance of Firmicutes in the ear canal of GAD participants compared to that of the age- and sex-matched healthy controls (HC). Metagenomic sequencing showed that Pseudomonas aeruginosa were significantly increased at species-level in GAD patients. Furthermore, we observed the relative abundance of Pseudomonas aeruginosa was positively associated with elevated systemic inflammatory markers and the severity of disease, suggesting that these ear canal microbiota alterations might be correlated with GAD by activating the inflammatory response. Conclusions These findings indicate that microbiota-ear-brain interaction via upregulating inflammatory reaction involve in the development of GAD, as well as suggest that ear canal bacterial communities may be a target for therapeutic intervention.